ICTs’ Impact on Energy Consumption and Economic Growth in the Countries of Central Asia: An Empirical Analysis - Kurmanov, Nurlan; Bakirbekova, Aigul; Adiyetova, Elmira; Satbayeva, Aizhan; Rakhimbekova, Assel; Nabiyeva, Maral (International Journal of Energy Economics and Policy, 2025)
This paper examines the relationship between information and communication technologies (ICTs), energy consumption, and economic growth in Central Asian countries (Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan) from 1992 to 2022. Using an autoregressive distributed lag (ARDL) model, the study assesses the short-run effects of ICT and trade openness on economic development, addressing a gap in regional empirical research. The findings indicate a significant positive impact of ICTs on economic growth, particularly in Kazakhstan and Uzbekistan, where digitalization drives economic expansion. Trade openness is a key growth factor, underscoring the role of international trade in regional integration. Energy consumption is positively linked to GDP, reflecting industrial dependence on energy-intensive sectors, especially in Kazakhstan and Turkmenistan. Diagnostic tests confirm the model’s reliability, absence of autocorrelation, and parameter stability. However, the impact of ICTs varies across countries due to differences in digital infrastructure, institutional factors, and government policies. The study has limitations, including its focus on short-term effects and the need for further research on ICTs’ role in sustainable energy use. It contributes to the literature by emphasizing digital infrastructure expansion, digital inclusion strategies, and energy-efficient development in Central Asia.